2015
DOI: 10.4149/gpb_2015005
|View full text |Cite
|
Sign up to set email alerts
|

Carbosulfan-induced oxidative damage following subchronic exposure and the protective effects of N-acetylcysteine in rats

Abstract: Abstract. Carbosulfan (CB)-induced oxidative stress leads to the inevitable accumulation of free radicals and eventual alteration of antioxidant enzymes in various biological systems. The present study is designed to investigate the preventive effect of N-acetylcysteine (NAC) on carbosulfaninduced hepatic and renal dysfunction in rats. Rats exposed to CB and NAC were examined for toxicity by assessing various biochemical alteration and stress markers including in liver and kidney. Significant increases of bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…The decline of GSH content is in concordance with various in vivo and in vitro studies that have implicated GSH depletion in MCP-induced toxicity (Siddiqui et al 1990;Rao 2006;Dwivedi et al 2010). Further, NAC has been reported to increase cellular GSH levels both in vivo and in vitro studies against pesticides-induced oxidative stress in rat tissues (Mostafalou et al 2012;El-Bini Dhouib et al 2015;Galal et al 2019). We also observed signi cant augmentation of GSH content by prior oral administration of NAC to the MCP exposed group.…”
Section: Discussionsupporting
confidence: 69%
“…The decline of GSH content is in concordance with various in vivo and in vitro studies that have implicated GSH depletion in MCP-induced toxicity (Siddiqui et al 1990;Rao 2006;Dwivedi et al 2010). Further, NAC has been reported to increase cellular GSH levels both in vivo and in vitro studies against pesticides-induced oxidative stress in rat tissues (Mostafalou et al 2012;El-Bini Dhouib et al 2015;Galal et al 2019). We also observed signi cant augmentation of GSH content by prior oral administration of NAC to the MCP exposed group.…”
Section: Discussionsupporting
confidence: 69%
“…NAC is found to protect rats by lowering the rate of glyphosate-mediated apoptosis and oxidative stress in testis (Bhardwaj et al, 2021), liver, kidney, and brain tissues (Turkmen et al, 2019). Many pesticides' toxicity is mitigated by NAC such as organophosphate compounds (Osman et al, 2021), alpha-cypermethrin (Arafa et al, 2015), carbamates (Dhouib et al, 2015), and imidacloprid (Hussein et al, 2018). Several studies have shown that NAC improves mitochondrial function and reduces behavioral deficits in the R6/1 mouse model of Huntington's disease (Wright et al, 2015), enhances mitochondrial reduced glutathione (mtGSH) content and mitochondrial function in oligodendroglia (Zhou et al, 2021), and protects mitochondria from oxidative injury (Kuo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Also, NAC improves the viability of human hepatocytes and protects the liver [21] and kidneys [22] against oxidant damage. NAC has an ameliorative effect against many pesticides toxicity such as organophosphate compounds (Yurumez et al, 2007; [23][24][25], alpha-cypermethrin [26], carbamates [27], and imidacloprid [28]. Accordingly, the present study was aimed to investigate the protective effect of NAC on hepato-nephro-toxicity induced by MX in male rats.…”
Section: Introductionmentioning
confidence: 98%